Resettlement after short prison sentences: What might work in England and Wales? - Raynor, Peter (Probation journal, 2020)
One of the advertised aims of the ‘Transforming Rehabilitation’ (TR) reforms in England and Wales was to extend compulsory post-custody supervision to prisoners serving short sentences who were outside the scope of existing resettlement provision. It is now well established that the arrangements introduced by TR for this group of prisoners have not been successful, having delivered high and often unmanageable caseloads, little help to service users and a greatly increased chance of recall to prison. The need which the reforms purported to meet remains unmet. There is little point in poorly designed and delivered provision; on the other hand, resources for the foreseeable future are not likely to support large increases in expenditure when so many parts of the criminal justice system require investment. This article draws on research from the 1990s onwards on provision for this group of prisoners, and in particular, the ‘Pathfinder’ projects of 1999–2003, as examples of what can be achieved on a voluntary basis. It is suggested that future provision for this group in England and Wales should be based on a more selective and individualized provision, with less coercion and more choice for service users.